The Effect Of Work Environment, Work Motivation, And Work-Life Balance On Employee Work Productivity In The Human Resources Department Of RSUPN Dr. Cipto Mangunkusumo In 2025 - Citra Setyaningrum; Fajar Saputra; Cici Demiyati (CV. AFDIFAL MAJU BERKAH, 2026)
Work productivity is an important indicator in assessing employee performance within an organization. Productivity is influenced by several factors, including work environment, work motivation, and work life balance. A supportive work environment, high work motivation, and a good balance between work and personal life can enhance employee productivity. This study aims to determine the effect of work environment, work motivation, and work life balance on employee work productivity in 2025. This study was a quantitative study using a cross-sectional design. The population and sample consisted of employees who met the inclusion criteria, with a total sampling technique involving 69 respondents. The research instrument used a Likert-scale questionnaire. Data were analyzed using univariate and bivariate analysis with multiple linear regression tests. The results showed that work environment, work motivation, and work life balance simultaneously had a significant effect on work productivity (p < 0.05). Partially, work motivation was the most dominant variable influencing work productivity. There is a significant effect of work environment, work motivation, and work life balance on employee work productivity.